Perancangan Sistem Informasi Pengelolaan Keuangan Berbasis Microsoft Excel pada TK Islam Amalia - Siti Nurchaliza; Diah Armeliza; Ayatulloh Michael Musyaffi (INDO PUBLISHING, 2025)
This study aims to design a financial management information system based on Microsoft Excel for TK Islam Amalia in order to improve the efficiency and effectiveness of financial recording and reporting. In addition, the study analyzes the existing financial management practices and evaluates user perceptions of the developed system using the Technology Acceptance Model (TAM). This research employs a Research and Development (R&D) method with the ADDIE model, consisting of the analysis, design, and development stages. Data collection techniques include structured interviews, observation, and documentation. The results indicate that financial management at TK Islam Amalia is still conducted manually and does not follow a standardized accounting cycle, such as journal entries, ledgers, and comprehensive financial reports. This is mainly due to limited human resources and a lack of understanding of financial applications. The Excel-based system designed in this study helps users to automatically record transactions, prepare more structured financial reports, and improve the ease and accuracy of financial recording. The findings emphasize the importance of improving financial management systems, enhancing user understanding, and optimizing the use of simple technology to support effective and accountable financial management at TK Islam Amalia in the future.